THE VALIDATION OF THE PEDIATRIC INCONTINENCE QUESTIONNAIRE (PINQ): A QUALITY OF LIFE MEASUREMENT SPECIFIC TO CHILDREN WITH BLADDER DISFUNCTION IN TURKEY - Akdemir, Aslihan; Dursun, Ismail; Coskun, Seda; Yel, Sibel; Nalcacioglu, Hulya; Dursun, Jale; Dusunsel, Ruhan (Springer, 2018)
[Abstract Not Available]